Summary of the research The effect of competition effort on the circulatory system response and the level of cortisol and lactic acid in the blood for advanced wrestlers - Shuaib, Jamal Mohammed; Judy, Suzan Khalifa; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The research aimed to identify the differences in the circulatory system response and the level of the cortisol hormone and lactic acid in the blood for the two groups between the two tests before and after the performance of the competition effort, in addition to identifying the differences in the circulatory system response and the level of cortisol and the lactic acid in the blood for the two groups between tests after the competition effort, The researchers used the descriptive method in the survey method in order to suit it to solve the research problem, as the research sample was chosen intentionally from free and Roman wrestling players applying in Diyala province for the weight category (60 - 67 - 72) kg (12) wrestlers out of (18) wrestlers and included two groups, (6) players from free wrestling and they are the first group, and (6) players from Roman wrestling are the second group, and for each weight of wrestlers (2) Wrestlers, and that constituted the percentage of the sample (66,666%) of the original community, as well as the use of appropriate means, tools and devices, and the exploratory experiment was conducted, after which the main experiment was conducted through tests before the effort and then a complete match was made for each wrestler with the same weight of the research and match sample It consists of two rounds, each round of (3) minutes duration, between them (30) seconds, is the competition effort Promise to conduct their own tests look after the competition effort, and then the data was unloaded and processed statistically, and then presented and analyzed and discussed, and the researchers reached several conclusions, namely : The effect of competition effort on the response of the circulatory system and the level of cortisol and lactic acid in the blood of the two groups compared to the period before the competition effort • The continuous training of the two groups led to a case of functional adaptation and consequently its effect was evident in the measurements of the circulatory system response and the level of cortisol and lactic acid in the blood . • The two groups were affected by the competition effort through the response of the circulatory system and the high level of the cortisol hormone and lactic acid in the blood with small differences and they were in favor of the free wrestling group . The researchers reached several recommendations : • Emphasis on special endurance training during the training units for its major role in improving the functional adaptations of the athlete’s body . • Perform periodic checks for players in order to continue the success of the training process • Carrying out similar research on different samples and other functional